Timing and intensity of exposure to interferon‐γ critically determines the function of monocyte‐derived dendritic cells. Issue 1 (September 2014) - Kerkar, Sid P.; Chinnasamy, Dhanalakshmi; Hadi, Neima; Melenhorst, Jan; Muranski, Pawel; Spyridonidis, Alexandros; Ito, Sawa; Weber, Gerrit; Yin, Fang; Hensel, Nancy; Wang, Ena; Marincola, Francesco M.; et al.
Summary A growing body of evidence suggests that inflammatory cytokines have a dualistic role in immunity. In this study, we sought to determine the direct effects of interferon‐γ (IFN‐γ) on the differentiation and maturation of human peripheral blood monocyte‐derived dendritic cells (moDC). Here, we report that following differentiation of monocytes into moDC with granulocyte–macrophage colony‐stimulating factor and interleukin‐4, IFN‐γ induces moDC maturation and up‐regulates the co‐stimulatory markers CD80/CD86/CD95 and MHC Class I, enabling moDC to effectively generate antigen‐specific CD4+ and CD8+ T‐cell responses for multiple viral and tumour antigens. Early exposure of monocytes to high concentrations of IFN‐γ during differentiation promotes the formation of macrophages. However, under low concentrations of IFN‐γ, monocytes continue to differentiate into dendritic cells possessing a unique gene‐expression profile, resulting in impairments in subsequent maturation by IFN‐γ or lipopolysaccharide and an inability to generate effective antigen‐specific CD4+ and CD8+ T‐cell responses. These findings demonstrate that IFN‐γ imparts differential programmes on moDC that shape the antigen‐specific T‐cell responses they induce. Timing and intensity of exposure to IFN‐γ can therefore determine the functional capacity of moDC.